Studi Literatur pada buku pemikiran pendidikan Islam di perguruan tinggi keagamaan Islam - Maya, Rahendra; Sarbini, Muhammad; Sarifudin, Sarifudin (Ta'dibuna: Jurnal Pendidikan Islam, 2019)
This study seeks to describe the literature books that examine the thinking of Islamic education figures in the frame of Islamic Education Thought which is widely used as a reference and popular in various Islamic religious colleges, both state and private, which are generally used by the Faculty of Tarbiyah and Teacher Training or various departments and study programs that are under its auspices. From at least 15 literary books on Islamic education figures' thoughts that have been successfully traced and then further examined the substance of their contents, nine books are more feasible and better to be used as references or become primary sources. While the other six books can be used as support or secondary sources. The most original primary source is, of course, the original work of the character that is used as the object of study and is to be explored by the roots of Islamic education. Abstrak Penelitian ini berupaya untuk mendeskripsikan buku-buku literatur yang mengkaji pemikiran para tokoh pendidikan Islam dalam bingkai Pemikiran Pendidikan Islam yang banyak dijadikan referensi dan popular di pelbagai perguruan tinggi keagamaan Islam, baik yang berstatus negeri maupun swasta, dimana umumnya digunakan oleh Fakultas Tarbiyah dan Ilmu Keguruan atau berbagai jurusan dan program studi dalam naungannya. Dari sedikitnya 15 buku literatur tentang pemikiran tokoh pendidikan Islam yang berhasil ditelusuri dan kemudian dikaji lebih lanjut substansi isinya berupa arkeologi pemikiran tokoh pendidikan Islam, terdapat sembilan buku yang lebih layak dan lebih baik untuk dijadikan referensi atau sebagai sumber primer. Sedangkan enam buku lainnya dapat dijadikan sebagai literatur penunjang atau sumber primer. Sumber primer yang paling orisinil tentunya adalah karya asli dari tokoh yang dijadikan sebagai objek kajian dan hendak digali akar pemikiran pendidikan Islamnya.